Implementation of Think Pair Share Cooperative Learning Model with Pop-Up Book Media to Improve Science Learning Outcomes - Dwi Rustanti; Nuril Huda; Muhajir Muhajir (PT. Anagata Sembagi Education, 2025)
This study aims to improve the learning outcomes of IPAS classes 3A and 3B at Pepe State Elementary School by using the Think Pair Share Type Cooperative Learning Model with Pop Up Book Media. The background of this study is the low average value of IPAS learning outcomes in both classes 3-A and 3-B at Pepe State Elementary School. This research uses a type of experimental quantitative research with a pre-Experimental Designone-Group (Pretest-Posttest Design) research design. The population in this study consisted of 29 students of class 3-A who were used as the experimental group and 28 students of class 3-B as the control group. In this study there was a significant increase in learning outcomes and critical thinking in the experimental group using the Think Pair Share Cooperative Learning Model with Pop Up Book media, namely from an average value of 60 to 78.46 or an increase of 18.46. While the control group also increased but not too significant from 60.35 up to 74.46 or up 14.16. While the results of the significance value between learning outcomes and critical thinking with the Think Pair Share Model approach with the help of Pop up book media <0.05, namely 0.045 and 0.018 which means there is a significant relationship. From the results of these results it can be concluded that the use of the Think Pair Share Cooperative Learning Model using Pop Up Book media can increase the learning value and critical thinking of 3A class students at Pepe State Elementary School..